Book Review: Big Data in Small Business. Data-Driven Growth in Small and Medium-Sized Enterprises, C. Lund Pedersen, A. Lindgreen, T. Ritter, T. Ringberg (Edited By), Edward Elgar Publishing, 2021 - Curina, Ilaria (Piccola Impresa / Small Business, 2025)
The book critically examines how small and medium-sized enterprises (SMEs) can exploit big data to enhance strategic decision-making, operational efficiency, and competitiveness. Through expert contributions and in-depth case studies, it addresses key themes such as human capital analytics, digital transformation, and data-driven learning. The book emphasizes practical, scalable solutions for SMEs to overcome resource limitations and integrate data analytics into their business models. By providing a comprehensive framework, it equips SMEs with tools to effectively promote sustainable growth and innovation in an increasingly data-centric global market.